DRINKING WATER DEMAND ANALYSIS AND MASTER PIPE NETWORK SIZE PLANNING IN UNGASAN VILLAGE, SOUTH KUTA SUBDISTRICT, BADUNG REGENCY - Ida Bagus Made Baskara Andika; I Nyoman Ariaputra (Universitas Udayana, 2024)
Ungasan Village is located in South Kuta District of Badung Regency, where the demand for water increases over time and the increase in tourism accommodation. Perumda Tirta Mangutama is an agency that provides water in the Badung area including Ungasan village, because Ungasan village is located in a topographic and geological structure composed of limestone rocks which makes other springs difficult to find. In the service by Perumda Tirta Mangutama, there are problems caused by the uneven and optimal pipe network currently owned, resulting in disrupted services such as dead water and people who still rely on tank water to fulfill their water needs. This study aims to analyze water demand and plan the optimal size of the main pipe network to serve the people of Ungasan village. The results of the analysis of Ungasan village population projections using the Least Square method until 2033 are 19,799 people, with a maximum day demand of 49.4975 liters / second. The main pipe planning is divided into 3 segments with the selection of main pipe locations based on public roads based on their function with a diameter of 10 inches and 8 inches.